Student Perceptions of Game Variation on Basketball Learning Outcomes - Apriyadi, Irwansyah; Lanos, Muhsana El Cintami; Handayani, Widya (Journal of Social Work and Science Education, 2023)
Learning basketball games is a team game that exists in physical education subjects, basketball games have many basic techniques that students must master. Game variations are a form of various kinds of basketball learning that is fun in various forms of games. The learning process does not all go well, one of the problems that occur during the learning process is either caused by inappropriate learning methods or approaches. The purpose of this study was to determine students' perceptions of game variations on basketball learning outcomes. The population in this study was grade VII students of State Junior High School 1 Lubuklinggau with a sample of 38 students used. Data collection in this study used questionnaires shared through Google forms. Based on the results of the analysis data, it is said that students' perceptions of game variations get a good response, students are happier and more motivated to follow learning if given many game variations. With the perception of (1) Student Interest obtained a score of 81.05% with a very good category, (2) Student Sincerity in basketball learning obtained a score of 83.82% with a very good category, (3) Student needs developed a variety of basketball learning obtained a score of 95.25% with a very good category. Of the total students, they said that they were happy because they were given a variety of games so that the material provided was easy to understand.